Diseño de una reingeniería de los procesos en la florícola platinum roses cía. ltda., ubicada en la provincia de Cotopaxi, cantón Latacunga, parroquia Tanicuchi en el período del 1 de enero al 31 de diciembre del 2013 - Caiza Aimacaña, Luis Antonio (2015)
This research aims to design a Process of Re-engineering by using re-engineering techniques and strategies that are aimed at providing solutions to the problems since the poor processes is the main problem. The development work began with a data collection through a survey of processes to each department that makes up the farm where the problem was determined. Financial Accounting, Human Resources and Marketing, where processes that do not add value to the company by analyzing, diagnosing and prioritizing results that were obtained by conducting field research in the departments. Thus allow to proceed the redesign them in order to apply goals and objectives proposed by the organization. In this research new processes were designed to the achieve efficiency way; changes that would be imposed excellent results which can optimize costs, improve usability, achieve goals, evaluate goals set by the estate to satisfy the needs of customers. This way can ensure competitiveness and entering new markets….